Interferometric Surface Analysis of a Phase-Only Spatial Light Modulator for Surface Deformation Compensation - Abdelazeem, Rania M.; Agour, Mostafa; Elnaby, Salah Hassab (Photonics, 2025)
A spatial light modulator (SLM) is a key element in several applications, but it is subject to surface deformation due to manufacturing imperfections or environmental factors. Therefore, the current study aims to analyze and compensate for such deformations in a phase-only SLM using a Michelson interferometer. The recorded interferogram represents the interference between the wavefront reflected from the SLM surface (object wave) and a reference wave. Noise in the recorded interferogram can degrade the accuracy of phase measurements. Various digital filtering techniques were applied to improve the signal-to-noise ratio (SNR) of the interferogram. The filtered interferogram enabled accurate phase extraction through Fourier transform processing and side peak selection using a spatial carrier frequency method. Additionally, phase errors caused by the tilt of the reference beam were corrected. Thereafter, the conjugate of the corrected phase distribution was used to calculate a phase-only computer-generated hologram (CGH), which was displayed on the SLM to compensate for surface deformations. The effectiveness of the proposed compensation procedure was confirmed by a second phase measurement, which demonstrated improved SLM performance. This study highlights the impact of combining the interferometric techniques with digital processing for precise surface deformation analysis.